2015
DOI: 10.1016/j.rbmo.2014.09.017
|View full text |Cite
|
Sign up to set email alerts
|

GnRH agonist plus vaginal progesterone for luteal phase support in ICSI cycles: a randomized study

Abstract: He continues to supervise post-graduate degrees in Obstetrics and Gynecology and related subjects. He is also Clinical Director at the Egyptian IVF-ET Centre, Maadi, Cairo, Editor-in-Chief of the Middle East Fertility Society Journal and a regular reviewer for several international journals. He has organized scientific meetings in Egypt in collaboration with key European and American centres, and participated in many international meetings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 26 publications
1
14
0
1
Order By: Relevance
“…Figure summarizes the study inclusion process. Ten studies from 12 records were included in this review: two studies with two records each and eight studies with one record each. At the time of writing, of the potentially eligible records/studies, five studies (from five records) were awaiting classification and were not included; four of these are ongoing studies and one has unknown status.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Figure summarizes the study inclusion process. Ten studies from 12 records were included in this review: two studies with two records each and eight studies with one record each. At the time of writing, of the potentially eligible records/studies, five studies (from five records) were awaiting classification and were not included; four of these are ongoing studies and one has unknown status.…”
Section: Resultsmentioning
confidence: 99%
“…For the probability of live birth or ongoing pregnancy (Figure 2), evidence from eight studies examining 2776 women showed a relative risk (RR) of 1.26 (95% CI, 1.04-1.53; I 2 = 58%). Sensitivity analysis, excluding the studies that did not report live birth and those at high risk of bias, resulted in one study examining 181 women with an RR of 1.07 19 Ata (2008) 16 Inamdar (2012) 20 Isikoglu (2007) 17 Qublan (2008) 22 Tesarik (2006) 24 Yildiz (2014) (95% CI, 0.73-1.58). Subgroup analysis according to agonist and antagonist cycles was unable to explain the observed heterogeneity; however, the studies that did not observe any benefit of using GnRH agonist during the luteal phase were those that used an agonist protocol for COS, while the two studies that used a GnRH antagonist for the intervention protocol observed more ongoing pregnancies in the intervention group ( Figure S1).…”
Section: Synthesis Of Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, only in GnRH antagonist cycles a significant increase in the OP was observed (16). Subsequent studies demonstrated that LP GnRHa supplementation seemed to benefit the GnRH antagonist co-treated cycle (8, 16, 2527) more than the long GnRHa co-treated cycle (18, 19, 28). The main reason for this is the down-regulation of the pituitary, which is induced by the long GnRHa protocol (28).…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent studies demonstrated that LP GnRHa supplementation seemed to benefit the GnRH antagonist co-treated cycle (8, 16, 2527) more than the long GnRHa co-treated cycle (18, 19, 28). The main reason for this is the down-regulation of the pituitary, which is induced by the long GnRHa protocol (28). In support of this conclusion, Kung et al (29) recently verified that luteal GnRHa administration significantly increased clinical pregnancy and LB rates in GnRH antagonist co-treated patients, but not in patients undergoing a long GnRHa down-regulation protocol.…”
Section: Discussionmentioning
confidence: 99%